An Enhanced Parallel-Observer-Based Deadbeat Predictive Control Method for PMSM With Non-Sinusoidal Back-EMF - Lei Guo; Guangxu Zhou; Ningran Song; Mengmei Zhu; Yongyun Mu (IEEE Access, 2024)
This study presents an enhanced deadbeat predictive control (DPC) method for permanent magnet synchronous motor (PMSM) drive system. By taking the model parameter mismatch and harmonics induced by non-sinusoidal back electromotive force (EMF) into consideration, an improved predictive error model is presented. Then, a parallel-observer combining super-twisting sliding model observer (STSMO) and adaptive line neuron (ADALINE) is proposed to estimate the fundamental and sixth harmonic components of predictive error model. Furthermore, an enhanced parallel-observer based DPC method is proposed to design rotor current controller. The advantage is that the predictive error under non-sinusoidal back EMF is reduced and the sixth harmonic in current is suppressed obviously. Better predicting and tracking performance can be guaranteed compared with conventional DPC method. Finally, numerous simulation and experimental results are given to validate the effectiveness and robustness of proposed method. It can be seen from experiment results that the tracking offset is tiny and the sixth harmonic ratio of predictive error is reduced to 0.06%. It indicates that the harmonic suppression performance and suitability of proposed method are satisfactory.